2020
DOI: 10.1371/journal.pone.0242077
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and quality of life of patients with osteoarthritis pain: The sixth Korea National Health and Nutrition Examination Survey (2013–2015)

Abstract: Objectives This study aims to investigate the association between mental health and quality of life of osteoarthritis (OA) patients according to the site of pain. Design Retrospective cross-sectional study Participants Data of 22,948 participants of the sixth Korea National Health and Nutrition Examination Survey conducted from 2013–2015 were used. Outcome measures Participants were asked if they had OA pain in the hip joint, knee joint, and lower back (yes/no) and whether they experienced anxiety or dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…Apart from ethnicity, this study also revealed that individuals who experienced pain involving back to lower limb region have a poorer HRQoL. This is consistent with the previous studies which suggest that HRQoL among patients with low back and knee pain is generally poorer [ 38 40 ]. Pain in the back and lower limbs commonly limits one’s physical function and mobility [ 41 , 42 ], and affects one’s capacity to work [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Apart from ethnicity, this study also revealed that individuals who experienced pain involving back to lower limb region have a poorer HRQoL. This is consistent with the previous studies which suggest that HRQoL among patients with low back and knee pain is generally poorer [ 38 40 ]. Pain in the back and lower limbs commonly limits one’s physical function and mobility [ 41 , 42 ], and affects one’s capacity to work [ 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Pain is the symptom that forces patients to seek medical advice and contributes the most to functional limitations and reduced quality of life [ 3 ]. Specifically, the impact of OA on the quality of life was found to be significantly associated with the sites of pain and sex [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metformin was found to effectively alleviate cartilage degradation and chondrocyte senescence by enhancing the polarization of AMPK and inhibiting mTORC1 [143]. miR-140 was shown to inhibit the expression of SA-β-Gal, p16 INK [4] a , and p21, effectively retarding chondrocyte senescence and attenuating the progression of OA [144]. Therefore, we speculate that OA chondrocytes are not senescent cells in the formal definition as they can proliferate in vitro.…”
Section: Cellular Senescencementioning
confidence: 89%
“…It has been estimated that the medical costs of OA account for about 1% to 2.5% of the US national gross domestic product and this number is expected to rise further with an aging population and the obesity epidemic [ 3 ]. In addition to physical impedance, OA also causes psychological stress, which may ultimately lead to social isolation and mental stress [ 4 ]. To date, there are no disease-modifying OA drugs (DMOADs) available to delay or reverse OA progression.…”
Section: Introductionmentioning
confidence: 99%